2013
DOI: 10.1111/gfl.12057
|View full text |Cite
|
Sign up to set email alerts
|

Pliocene sand injectites from a submarine lobe fringe during hydrocarbon migration and salt diapirism: a seismic example from the Lower Congo Basin

Abstract: International audienceLarge-scale conical and saucer-shaped sand injectites have been identified in the Upper Miocene sediments of the Lower Congo Basin. These structures are evidenced on the 3D high-resolution seismic data at about 600 ms TWT (two-way traveltime) beneath the seabed. The conical and saucer-shaped anomalies range from 20 to 80 m in height, 50 to 300 m in diameter, and 10 to 20 ms TWT in thickness. They are located within a sedimentary interval of about 100 m in thickness and are aligned over 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 92 publications
(275 reference statements)
0
15
0
Order By: Relevance
“…Smyers and Peterson, 1971;Truswell, 1972;Hiscott, 1979;Hillier and Cosgrove, 2002;Hubbard et al, 2007;Cartwright et al, 2008;Monnier et al, 2014), sometimes downward (e.g. Gottis, 1953;Parize, 1988;Huang, 1988;Scholz, 2009Scholz, , 2010, and rarely in all directions (Philips and Alsop, 2000;Surlyk, 2001Surlyk, , 2007Rowe et al, 2002;Ribeiro et Terrinha, 2007).…”
Section: Models Of Sand Injectionmentioning
confidence: 99%
“…Smyers and Peterson, 1971;Truswell, 1972;Hiscott, 1979;Hillier and Cosgrove, 2002;Hubbard et al, 2007;Cartwright et al, 2008;Monnier et al, 2014), sometimes downward (e.g. Gottis, 1953;Parize, 1988;Huang, 1988;Scholz, 2009Scholz, , 2010, and rarely in all directions (Philips and Alsop, 2000;Surlyk, 2001Surlyk, , 2007Rowe et al, 2002;Ribeiro et Terrinha, 2007).…”
Section: Models Of Sand Injectionmentioning
confidence: 99%
“…Clastic injectites occur stratigraphically beneath the parent sandstone, with net lateral propagation towards and beyond the margin of the parent sandstone lobe complex. In other examples, where injectites of seismic‐scale are known to be sourced from lobe complexes (as observed in intra‐slope lobes), the source point is the proximal lobe (complex) fringe (Yang & Kim, ; Spychala et al ., ), or the lateral lobe margin pinchout (Monnier et al ., ). In the latter case, the lobe reaches its highest point laterally.…”
Section: Discussionmentioning
confidence: 97%
“…However, the distribution of subseismic scale injectites and their relationship with those of a seismic‐scale are poorly understood (Hurst & Cartwright, ). The literature is dominated by examples of clastic injectites that are associated with primary deposits on a slope setting, such as deep marine channel‐fills (Hiscott, ; Dixon et al ., ; Rowe et al ., ; Parize & Friès, ; Duranti & Hurst, ; Huuse et al ., ; Diggs, ; Duranti, ; Frey‐Martínez et al ., ; Hamberg et al ., ; Jackson, ; Jonk et al ., ; Surlyk et al ., ; Vigorito et al ., ; Kane, ; Svendsen et al ., ; Szarawarska et al ., ; Jackson et al ., ; Løseth et al ., ; Morton et al ., ; Bain & Hubbard, ) and intraslope lobes (Monnier et al ., ; Yang & Kim, ; Spychala et al ., ). In cases where the parent sand cannot be directly constrained, regional context still suggests that injectites were originally sourced from a submarine slope sandbody (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that hydraulic fracturing is most likely responsible for the shape of the observed seismic chimney, given the small‐scale fracturing and the limited spatial extent of the SE‐NW oriented structurally disturbed zone. Overpressure in the reservoir may initiate local deformation of sedimentary strata, and overpressured sand bodies may also cause injection of fluidized sand into overlying strata in the course of hydraulic fracturing (Cartwright et al, ; Hurst et al, ; Monnier et al, ; Shoulders & Cartwright, ). This movement of sand typically leads to an uplift of overlying strata and conical intrusions.…”
Section: Discussionmentioning
confidence: 99%
“…Research focused on the geological setting of fluid migration pathways (Andresen et al, ; Cartwright et al, ; Serié et al, ) and the formation of seafloor seepage features in particular (Cathles et al, ; Ho et al, ; Sultan et al, , ). In association with hydrocarbon migration, the interaction of sand injectites with fluid flow systems has been investigated specifically (Cartwright et al, ; Hurst et al, ; Monnier et al, ; Shoulders & Cartwright, ). Such sand bodies have been attributed to overpressure due to tectonic stress, leading to the deformation of overlying sediments and the formation of hydrocarbon migration pathways through former seals.…”
Section: Introductionmentioning
confidence: 99%